Factors Associated With COVID-19 Breakthrough Infections in Large Midwestern Healthcare System: Implications for Vulnerable Healthcare Personnel. Issue 8 (9th August 2022) - Rivelli, Anne; Fitzpatrick, Veronica; Copeland, Kenneth; Richards, Jon
Abstract : Study findings underline the significance of initiating booster vaccination among all HCP, particularly groups at higher risk. Healthcare systems need to continue to support and protect vulnerable HCP, including appropriate and sufficient PPE, versatile sick leave and exposure policies, increased testing and symptom monitoring, and potential incentives for booster vaccines. Abstract : Objective: The aim of the study is to identify factors associated with breakthrough infection among a cohort of Midwestern healthcare personnel (HCP). Methods: SARS-CoV-2–positive test results between March 1, 2020, and July 31, 2021, were collected from electronic medical records of HCP to identify breakthrough infections. Results: Healthcare personnel who were younger than 35 years, received the Pfizer vaccine, and worked in COVID clinical units had greater adjusted odds of breakthrough infection. COVID infection before full vaccination was associated with reduced odds of breakthrough infection. Conclusions: Our study concluded that the most vulnerable HCP are younger, working in COVID-19 clinical units, and received Pfizer-BioNTech primary series vaccines. Healthcare personnel who had COVID before vaccination were at reduced risk of breakthrough infection, indicating that supplemental immunity could better protect at-risk HCP groups.